Pseudobranchiomysis arenae, a new genus and species of Leptomysinae (Crustacea: Mysida) in Argentinian sandy beaches - Carcedo, Cecilia; Fiori, Sandra; Hoffmeyer, Mónica (Zootaxa, 2013)
A new genus of Leptomysinae Hansen, 1910, constituting a new type species for science, is described: Pseudobranchio-mysis arenae. This new mysid is characterized by a combination of the following characters: antennal scale lanceolate and setose all around with a pointed apex, telson with apical cleft armed with many fine spines on the convex margins, and well-developed pseudobranchial lobes in male pleopods. Individuals of this species were found in the surf zone of two sandy beaches in Argentina and constitute a stable population.